2011
DOI: 10.1002/pon.1730
|View full text |Cite
|
Sign up to set email alerts
|

Discussion of emotional and social impact of cancer during outpatient oncology consultations

Abstract: Low prevalence of discussion of psychosocial issues cannot be accounted for by patient or clinician communication preferences. If clinicians rely on patients to initiate discussion of psychosocial issues, patients' problems may go unaddressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 24 publications
1
46
0
2
Order By: Relevance
“…Prior studies also suggest there are particular challenges to increasing trainees' skill in responding to affective aspects of communicating bad news. 26 Two other recent studies have reported similar difficulties with improving trainees' ability to explore patient emotions in response to bad news. 15,16 One of these was a randomized trial 15 and the other was a training program for end-of-life communication with physician trainees in Australia.…”
Section: Discussionmentioning
confidence: 95%
“…Prior studies also suggest there are particular challenges to increasing trainees' skill in responding to affective aspects of communicating bad news. 26 Two other recent studies have reported similar difficulties with improving trainees' ability to explore patient emotions in response to bad news. 15,16 One of these was a randomized trial 15 and the other was a training program for end-of-life communication with physician trainees in Australia.…”
Section: Discussionmentioning
confidence: 95%
“…Tedaviyle ilişkili fiziksel ve sosyal sorunları, tekrarlama riskinden dolayı korku, anksiyete ve depresyon gibi duygusal sıkıntıları bilmek istemektedirler. [18,19] Bu aşamada hastaların baş etme stratejilerini öğrenmeleri önemlidir. [13,16] Birey olarak sağlık profesyonelleri tarafından hatırlanmak anksiyetelerinin azalmasına yardımcı olabilir.…”
Section: Introductionunclassified
“…[12] Ayrıca hastaların eğlence aktiviteleri, aile konuları ve tatiller gibi sosyal konular hakkında bilgi ve desteğe gereksinimleri vardır. [19] Hastalar hemşireden hakkını savunmasını [15] ve duygularını paylaşmasını istemektedir. [16] Hastaların yeni durumu anlamak ve özümsemek için desteğe gereksinimleri vardır.…”
Section: Introductionunclassified
“…consultation), female patients with female oncologists were more likely to encourage empathic responses from clinicians [17]. Emotion-related quality of life of cancer patients has also been indicated as a predictor influencing the discussion around emotion during consultations [14]. There is little evidence showing how HNC patients' emotional wellbeing might relate to the dynamics of emotional discussion with their clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom, the National Institute for Clinical Excellence (NICE) guidelines recommended that the psychosocial issues are routinely assessed and discussed in oncology practice [7]. Despite recognised patient benefits, national efforts and many communication training programmes [8,9], research evidence suggests a continued prevalence of unaddressed psychological issues among cancer patients [10][11][12][13][14]. It is, therefore, important to intricately investigate factors influencing oncologists' positive responses to patients' negative emotions in routine oncology practice.…”
Section: Introductionmentioning
confidence: 99%